2014
DOI: 10.1017/s1049023x14000533
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Symptoms and Food/Nutrition Concerns after the Great East Japan Earthquake in March 2011: Survey of Evacuees in a Temporary Shelter

Abstract: On March 11, 2011, a 9.1 magnitude earthquake occurred in the eastern Pacific Ocean off the coast of northern Japan. A resulting tsunami struck the Japan Pacific coast, causing >20,000 deaths, injuries and missing persons. Survivors' post-tsunami health and nutritional status were surveyed one month after the disaster in a school shelter in Ishinomaki City. Hyogo College of Medicine's disaster relief team observations and survivors' questionnaires were used to assess the disaster's effects on survivors' lifest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 6 publications
0
40
0
Order By: Relevance
“…Temporary toilet supplies, manual hygiene with alcohol gel, designation of cooking and shoesoff areas, and supplies of temporary bathing were push-type support countermeasures supplied from outside. Promoting the nutrition of affected people is another important countermeasure designed to increase resistance to infectious disease (Inoue et al 2014). The age/gender-specific rate indicates an increase of the two types of infectious disease above in all age/gender groups (Fig.…”
Section: Infectious Diseasementioning
confidence: 99%
“…Temporary toilet supplies, manual hygiene with alcohol gel, designation of cooking and shoesoff areas, and supplies of temporary bathing were push-type support countermeasures supplied from outside. Promoting the nutrition of affected people is another important countermeasure designed to increase resistance to infectious disease (Inoue et al 2014). The age/gender-specific rate indicates an increase of the two types of infectious disease above in all age/gender groups (Fig.…”
Section: Infectious Diseasementioning
confidence: 99%
“…This is because Nepal has a high altitude (1400 m), great temperature difference between the day and night (from 6 to 28 ), changeable weather, a lot of rain after earthquake, shortage of supplies and weak warmth retention measures. Inoue et al 6 reported that 23% of the disaster survivors would have weight lost because of the insufficient food variety and digestive dysfunction by stress. The difficult transportation and food shortage in the earthquake-stricken areas in Nepal led to an increased incidence of malnutrition.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…These situations take longer to resolve, and survivors are often evacuated to shelters or evacuation centers. In shelters, long-term evacuees complain of numerous health problems, including infectious disease, pain, insomnia, or chronic disease (Inoue et al, 2014;Tokuda et al, 2014). The Japanese Medical Association Team, the Disaster Relief Project Team of the Japanese Primary Care Association, and other multi-disciplinary medical assistance teams provide medical support.…”
Section: Introductionmentioning
confidence: 99%